Disease Specific Bacterial Communities in a Coralline Algae of the Northwestern Mediterranean Sea: A Combined Culture Dependent and -Independent Approach - Quéré, Gaëlle; Intertaglia, Laurent; Payri, Claude; Galand, Pierre E. (Frontiers in Microbiology, 2019)
Crustose coralline red algae (CCA) are important components of marine ecosystems thriving from tropical waters and up to the poles. They fulfill important ecological services including framework building and induction of larval settlement. Like other marine organisms, CCAs have not been spared by the increase in marine disease outbreaks. The white-band syndrome has been recently observed in corallines from the Mediterranean Sea indicating that the disease threat has extended from tropical to temperate waters. Here, we examined the microbiome and the pathobiome of healthy and diseased Neogoniolithon brassica-florida coralline algae in the Mediterranean Sea by combining culture-dependent and -independent approaches. The coralline white-band syndrome was associated with a distinct pathobiome compared to healthy tissues and showed similarities with the white-band syndrome described in the Caribbean Sea. A sequence related to the genus Hoeflea, order Rhizobiales, characterised the white-band disease pathobiome described by amplicon sequencing. No representative of this genus was isolated by culture. We, however, successfully isolated an abundant member of the healthy CCA microbiome, an Alphaproteobateria of the family Rhodobacteraceae. In conclusion, we did not identify a potential causative agent of the disease, but through the complementarity culture dependent and independent approaches we characterised the healthy microbiome of the coralline and the possible opportunistic bacteria colonizing diseased tissues.